Structural Equation Model of Tourist Loyalty toward Dvaravati Civilization Tourist Attraction to be served as a Center of Western Creative Tourism - ruangkalapawongse, annop; Ruangkalapawongse, Sarawan (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2020)
This research aimed to study the influence on tourist loyalty towards Dvaravati civilization attractions and finding a guideline for creating the loyalty towards Dvaravati civilization attractions. These mixed methods combined with a quantitative and qualitative research. According to the results, it was found that the tourism motivation had a positive direct influence on the tourism satisfaction; the tourism image had a positive direct influence on the tourist loyalty; the tourism satisfaction had a positive direct influence on the tourist loyalty; and the tourism motivation had an indirect influence on the tourist loyalty through tourism satisfaction. With regard to the guideline for creating the loyalty towards the attractions, the operation should be carried out in 3-stage plan as follows: 1st Stage: Tourism improvement plan to attract tourists to visit Dvaravati civilization attractions, 2nd Stage: Tourism promotion plan to increase the number of tourists in Dvaravati civilization attractions, and 3rd Stage: Tourism sustainability development plan to attract new customer groups and increase the return rate of tourists which will affect the tourism and circular economy to be prosperous and sustainable to support the creative tourism center.